1998
DOI: 10.1161/01.atv.18.9.1371
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Activated Protein C in Healthy Subjects and Patients With Previous Venous Thromboembolism

Abstract: Abstract-The proteolytic enzyme activated protein C (APC) is a normal plasma component, indicating that protein C (PC) is continuously activated in vivo. High concentrations of homocysteine (Hcy) inhibit the activation of PC in vitro; this effect may account for the high risk for thrombosis in patients with hyperhomocysteinemia (HyperHcy). We measured the plasma levels of APC in 128 patients with previous venous thromboembolism (VTE) and in 98 age-and sex-matched healthy controls and correlated them with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
26
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 26 publications
5
26
2
Order By: Relevance
“…To confirm the onset of a prethrombotic state, clinical studies have been performed in hyperhomocysteinemic patients. Some abnormal plasma elevations of hemostatic parameters, including factor VIII (Freyburger et al, 1997), von Willebrand factor (van den Berg et al, 1995), fibrinogen (von Eckardstein et al, 1994), thrombomodulin (van den Berg et al, 1995), thrombin/antithrombin III complex and activated protein C (Cattaneo, 1999;Cattaneo et al, 1998), and type 1 plasminogen activation inhibitor (Freyburger et al, 1997) have been reported. However, the increase of the anticoagulant effectors is inconsistent with a prothrombotic environment.…”
Section: Alterations Of Vascular Thromboresistancementioning
confidence: 99%
“…To confirm the onset of a prethrombotic state, clinical studies have been performed in hyperhomocysteinemic patients. Some abnormal plasma elevations of hemostatic parameters, including factor VIII (Freyburger et al, 1997), von Willebrand factor (van den Berg et al, 1995), fibrinogen (von Eckardstein et al, 1994), thrombomodulin (van den Berg et al, 1995), thrombin/antithrombin III complex and activated protein C (Cattaneo, 1999;Cattaneo et al, 1998), and type 1 plasminogen activation inhibitor (Freyburger et al, 1997) have been reported. However, the increase of the anticoagulant effectors is inconsistent with a prothrombotic environment.…”
Section: Alterations Of Vascular Thromboresistancementioning
confidence: 99%
“…In some of these patients, platelets that produce normal amounts of thromboxane A 2 fail to respond to the agonist because of defects in the corresponding receptor, but in many others the pathogenetic mechanism is poorly defined (12). Thus, congenital P2Y 12 defects may be more common than presently recognized, but they may be mistakenly identified with other disorders of platelet function (13).The P2Y 12 locus has been analyzed in some patients in whom the platelet binding sites for ADP and the nonhydrolyzable ADP analogue 2-methylthioadenosine 5Ј-diphosphate (2MeS-ADP) were reduced by 70-80% (7,11,14). In two instances, different homozygous frameshift mutations were found to cause premature termination of translation.…”
mentioning
confidence: 99%
“…The other, P2Y 12 , is negatively coupled to adenylyl cyclase through G i ; it mediates progressive and sustained platelet aggregation in the absence of shape change (2, 3, 5) and plays an important role in the potentiation of secretion induced by several agonists (6, 7). P2Y 12 is the therapeutic target of ticlopidine and clopidogrel (8), two platelet aggregation inhibitors used for the prevention and treatment of arterial thrombosis (9), and its congenital deficiency results in a bleeding disorder (7,10,11). Platelets deficient in P2Y 12 exhibit normal ADP-induced shape change but only slight and rapidly reversible aggregation, as well as a failure of ADP to inhibit the rise of cAMP levels after stimulation with prostaglandin E 1 (PGE 1 ) (1).…”
mentioning
confidence: 99%
See 2 more Smart Citations